The role of cluster initiatives in supporting industry development - Balcerzak, Weronika Kinga; Pantea, Smaranda; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The thesis aims to analyse the impact of a cluster on industry development. The aerospace industry was chosen for the analysis. The paper consists of three parts: a literature review, an analysis of the aerospace industry in the European Union and Poland, and a case study analysis of the Silesian Aviation Cluster. The first part is based on theoretical literature, reports of foreign organisations and empirical studies on clusters and aerospace clusters. The next part presents the analysis of Eurostat and Statistic Poland data. The final part analyses the benefits companies can get from being a cluster initiative member and whether it supports industry development. The conclusions drawn show a relation between being a member of the Silesian Aviation Cluster and a successful foreign expansion. However, the conclusions are based only on analysing one of four internationalisation projects as the other three are still running.
Vedoucí práce: Smaranda Pantea
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses